Modified technique for sacrospinous-sacrotuberous ligament complex colpopexy in apical prolapse: preliminary results of a pilot randomized study - Sweed, Mohamed S.; Mostafa, Hassan A.; Sammour, Hazem M.; Ashour, Hisham A.; Nadim, Mahmoud A.; Ibrahim, Osama I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Apical prolapse is frequently encountered following vaginal hysterectomy either or as a primary finding in patients with pelvic organ prolapse. This pilot comparative study introduces a modified sacrospinous sacrotuberous ligament fixation with biologic mesh augmentation which necessitates no special kits to be performed. Methods: This study was conducted at Department of Obstetrics and gynecology, Ain Shams University, Cairo, Egypt, and Department of Women Health of Bethanien Hospital, Iserlöhn, Germany from March 2018 to May 2020. 40 women with either utero-vaginal or vaginal vault prolapse were randomized to either; group (A): 20 women scheduled for modified sacrospinous-sacrotuberous fixation procedure, or group (B): 20 women scheduled for conventional sacrospinous-sacrotuberous fixation procedure. Results: Improvement of the Pelvic organ prolapse quantification system (POP-Q) stage from the base line pre-operative stage was 1 stage higher in the modified SS/ST-F group compared to the conventional SSF group (3 stage improvement from baseline in SS/ST-F group versus 2 stage improvement only in conventional SSF group). Conclusions: This pilot study provides a modified sacrospinous sacrotuberous ligament colpopexy technique which is easier to be performed and mastered, does not need the use of special devices, provides better improvement of grade of prolapse and less complications compared to the conventional technique.